Step-by-step explanation:
0
Answer:
x = 6
Step-by-step explanation:
Given
6x² - 2x + 36 = 5x² + 10x ( subtract 5x² + 10x from both sides )
x² - 12x + 36 = 0 ← in standard form
This is a perfect square of the form
(x - a)² = x² - 2ax + a²
36 = 6² ⇒ a = 6 and 2ax = (2 × 6)x = 12x, hence
(x - 6)² = 0
x - 6 = 0 ⇒ x = 6
Answer: a) √50
b) n = 1 + 7i
Step-by-step explanation:
first, the modulus of a complex number z = a + bi is
IzI = √(a^2 + b^2)
The fact that n is complex does not mean that n doesn't has a real part, so we must write our numbers as:
m = 2 + 6i
n = a + bi
Im + nI = 3√10
Im + n I = √(a^2 + b^2 + 2^2 + 6^2)= 3√10
= √(a^2 + b^2 + 40) = 3√10
a^2 + b^2 + 40 = 3^2*10 = 9*10 = 90
a^2 + b^2 = 90 - 40 = 50
√(a^2 + b^2 ) = InI = √50
The modulus of n must be equal to the square root of 50.
now we can find any values a and b such a^2 + b^2 = 50.
for example, a = 1 and b = 7
1^2 + 7^2 = 1 + 49 = 50
Then a possible value for n is:
n = 1 + 7i
Answer:
263.76
Step-by-step explanation:
The formula is pi(3.14) times r(radius squared) (6^2) times h(height)( 7) over 3
3.14 times 36 times 7/3
Answer:
81.5, 9, 180
Step-by-step explanation:
28.
c=9
9x9=81
a=1/2
81+1/2=81.5
29.
9x1/2=4.5
4.5x2=9
30.
15x15=225
9x5=45
225-45=180
hope this helps!!!